PERANCANGAN SISTEM APLIKASI PERHITUNGAN OTOMATIS BERBASIS VB NET DAN ARDUINO PADA MESIN CHAMBER DI PT JVCKENWOOD - Ahmad Zaenudin; Ahmad Anas (Jurnal Komputer dan Teknologi, 2025)
Technological advances are an important aspect for companies in meeting demands for ease, speed and accuracy of information processing. The Head Unit testing system at PT JVCKENWOOD ELECTRONICS INDONESIA currently still uses manual methods on several chamber machines, this is considered less effective because it takes a long time to set the stopwatch and does not provide test history data for each process (report). Based on these problems, the author aims to design an automatic calculation application system based on VB.NET and Arduino on the chamber machine at PT JVCKENWOOD ELECTRONICS INDONESIA. The results of research at PT JVCKENWOOD ELECTRONICS INDONESIA show that by building an automatic calculation system on the chamber machine, the process of recording test history can be made easier and the potential for timing errors on the stopwatch can be eliminated.